PENGARUH SALURAN DISTRIBUSI TERHADAP VOLUME PENJUALAN DI PT SINAR SOSRO KANTOR PENJUALAN RANGKASBITUNG LEBAK BANTEN (Studi Pada Merek Teh Botol Sosro) - Mia Nurul Hikmah Mia Nurul Hikmah; Atik Atiatun Nafisah Atik Atiatun Nafisah (NIAGARA Scientific Journal, 2017)
The purpose of this study was to determine the effect of distribution channels on sales volume at PT. Sinar Sosro Rangkasbitung Sales Office case study of the Sosro bottled tea brand. The independent variables studied are the distribution channels used consisting of: Agent Distribution Channels (X1), Semi-Agent Distribution Channels (X2) and Retailers (X3) with the dependent variable namely Sales Volume at PT. Sinar Sosro Rangkasbitung Sales Office brand of Sosro bottled tea. This research uses quantitative methods and descriptive analysis. The quantitative analysis method uses simple correlation analysis, multiple correlation and coefficient of determination. Descriptive analysis explains the inhibiting factors that influence the selection ofdistribution channels and efforts to overcome these obstacles at PT. Sinar Sosro Rangkasbitung Sales Office. The results of thequantitative analysis based on simple correlation, distribution channel variables to sales volume: Agent distribution channel (X1) with a correlation of -0.646 and a coefficient of determination of 41.7%. The semi-agent distribution channel variable (X2) is -0.118 and the coefficient of determination value is 1.4%. Retailer distribution channel (X3) with a correlation of 0.900, the coefficient of determination value is 81%. Independent variables (agent distribution channels, semi-agents, retailers) have a joint effect of 99.2% on the dependent variable (Sales Volume). The remaining 0.8% is influenced by other factors not included in this study. The results of descriptive research show that PT. Sinar Sosro Rangkasbitung Sales Office has obstacles in the selection of distribution channels, namely the relatively small number of purchases, its efforts to carry out a feasibility analysis and monitor distribution channels. The sales unit value is low, efforts to distribute products are made into trends and given to certain distribution channels. Changes in capital and the amount of distribution channel debt, efforts to provide assistance to distribution channels. Limited capital and facilities owned by distribution channels, efforts to provide assistance with capital facilities and policies are adjusted to the capabilities of distribution channels. Sales volume that does not reach the target, efforts to provide prizes to distribution channels that reach the target.